Stronger negative species interactions in the tropics supported by a global analysis of nest predation in songbirds - Matysioková, Beata; Remeš, Vladimír (Journal of biogeography, 2022)
Aim Species interactions are assumed to be stronger closer to the equator. However, numerous studies provided conflicting results and considerable controversy exists concerning the latitudinal patterns in the intensity of biotic interactions. Thus, the question of whether biotic interactions are stronger near the equator remains open. Here, we provide a global evaluation of latitudinal trends in nest predation in songbirds and their explanations. Location Worldwide. Taxon Songbirds (Aves: Passeriformes). Methods We collected published data on nest predation in 1297 populations of 659 species across the globe (124,958 nests). We quantified latitudinal trends in the intensity of nest depredation (daily predation rate, DPR) and in potential demographic impacts of nest depredation (the proportion of nests destroyed by predators). We also quantified the latitudinal trend in the proportion of failed nests destroyed by predators and assessed how nest depredation and latitudinal trends differed across nest types. We aimed at explaining spatial variation in nest predation by productivity and species richness of potential nest predators. Results All measures of nest predation increased towards the equator and the increase was stronger in the northern hemisphere. Nest predation also increased with time, and it was higher in open nests than in cavities. Nest predation increased with productivity (indexed by NDVI), independently of latitude. It also increased with species richness of potential nest predators, but this effect was confounded with latitude. Main conclusions Tropical songbirds faced both higher intensity of nest predation (higher DPR) and more detrimental demographic outcomes of nest depredation (higher proportion of nests lost to predators). Moreover, the proportion of nest failure caused by predators also increased towards the equator. Our results support the view that birds are subject to strong biotic interactions close to the equator. Nest predation increased with productivity and tended to increase with species richness of potential nest predators.